PhIP-Seq: unveiling the complexity of antibody repertoires in health and disease - Tang, Wenjie; Gai, Qijing; Yang, Junjie; Chen, Jianqing; Lyu, Zhengbing (Frontiers in Immunology, 2026)
Phage-Immunoprecipitation Sequencing (PhIP-Seq) merges phage display with next-generation sequencing to enable high-throughput profiling of antibody repertoires. This review synthesizes the technical evolution of the PhIP-Seq platform, critically assessing the workflow from peptide library design and immunoprecipitation to bioinformatics analysis. We evaluate strategies for optimizing library diversity and minimizing non-specific binding, while addressing inherent limitations such as the detection of conformational epitopes and post-translational modifications. The clinical utility of PhIP-Seq is examined through its application in identifying novel autoantigens in systemic lupus erythematosus and multiple sclerosis, mapping viral epitopes in SARS-CoV-2 and Plasmodium falciparum, and detecting tumor-associated antigens. Finally, we discuss the trajectory of the field toward integration with multi-omics datasets and the development of point-of-care diagnostic tools.